Coal mining waste dumps as secondary deposits – examples from the Upper Silesian Coal Basin and the Lublin Coal Basin - Gawor, Łukasz (Geology, Geophysics and Environment, 2015)
Polish coal mining industry generates approximately 30 million Mg of mining wastes per year, which represents the largest amount of industrial waste in Poland. This results in the disposal of a huge volume of wastes at waste dumps. The coal mining waste dumps are spread within the area of over 4,000 ha in more than 220 dumping sites, where over 760 million Mg of wastes from hard coal mining have been disposed. One of the most recent problems in Poland is the recovery of coal from mining waste. There is a possibility and necessity to recover coal from mining waste dumps, which should be linked with appropriate legal regulations.In this paper, distribution and dimensions of coal mining waste dumps in the Upper Silesian Coal Basin and the Lublin Coal Basin are analyzed. Selected problems of negative environmental impacts of coal mining wastes – that may be reduced by the recovery of coal – are presented. Legal regulations referring to the mining waste management are analyzed. Some examples of a successful recovery of coal mining dumps as well as economic feasibility studies are given. The analysis of potential objects, which are the most valuable in terms of recovery processes, is presented.Coal mining waste dumps may be considered as important secondary deposits. Feasibility studies and past experiences in the coal recovery show a need for new recovery sites. Sustainable coal recovery is not only economically but also ecologically justified. The re-using and managing of reclaimed dumping sites for local communities is also of importance.